2001
DOI: 10.1021/ja010744s
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Tetrakis(dimethylamide)−Titanium, −Zirconium and −Hafnium with Silanes:  Synthesis of Unusual Amide Hydride Complexes and Mechanistic Studies of Titanium−Silicon−Nitride (Ti−Si−N) Formation

Abstract: M(NMe(2))(4) (M = Ti, Zr, Hf) were found to react with H(2)SiR'Ph (R' = H, Me, Ph) to yield H(2), aminosilanes, and black solids. Unusual amide hydride complexes [(Me(2)N)(3)M(mu-H)(mu-NMe(2))(2)](2)M (M = Zr, 1; Hf, 2) were observed to be intermediates and characterized by single-crystal X-ray diffraction. [(Me(2)N)(3)M(mu-D)(mu-NMe(2))(2)](2)M (1-d(2), 2-d(2)) were prepared through reactions of M(NMe(2))(4) with D(2)SiPh(2). Reactions of (Me(2)N)(3)ZrSi(SiMe(3))(3) (5) with H(2)SiR'Ph were found to give amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…For each metal, both the M-C and M-Si bonds are shorter in the IMe complexes (1 and 2) than they are in the ItBu complexes (3 and 4) (Table 1). However, 1 and 2 also deviate more from linearity with C-M-Si bond angles of 171.91 (11)°and 171.6(2)°, for 1 (M = Cu) and 2 (M = Ag) respectively, than do 3 (178.60(5)°) and 4 (178.77(5)°). These differences may be due, in part, to the larger size of the ItBu ligand which leads to increased crowding around the metal center increasing the bond distances and pushing the ligands as far apart as possible in 3 and 4.…”
Section: Synthesis Of N-heterocyclic Carbene Metal-silyl Complexesmentioning
confidence: 86%
See 3 more Smart Citations
“…For each metal, both the M-C and M-Si bonds are shorter in the IMe complexes (1 and 2) than they are in the ItBu complexes (3 and 4) (Table 1). However, 1 and 2 also deviate more from linearity with C-M-Si bond angles of 171.91 (11)°and 171.6(2)°, for 1 (M = Cu) and 2 (M = Ag) respectively, than do 3 (178.60(5)°) and 4 (178.77(5)°). These differences may be due, in part, to the larger size of the ItBu ligand which leads to increased crowding around the metal center increasing the bond distances and pushing the ligands as far apart as possible in 3 and 4.…”
Section: Synthesis Of N-heterocyclic Carbene Metal-silyl Complexesmentioning
confidence: 86%
“…Based on the similar solid state structures obtained, all of the N-donor complexes (11)(12)(13)(14)(15) may be viewed as a cationanion pair of the form [L n M] + [M(Si(SiMe 3 ) 3 ) 2 ] − (M = Cu, Ag, n = 1, 2), where the anionic metal center interacts with the cationic center via the M-M contact. This view is supported by the observation that in complexes such as [K][Cu(Si(SiMe 3 ) 3 ) 2 ], an interaction between the Cu and K centers is observed.…”
Section: Synthesis Of Metal-silyl Complexes Containing N-donorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, M(NMe 2 ) 4 (M=Zr, Hf) were found to react with silanes to give aminosilanes and unusual amide–hydride complexes [{(Me 2 N) 3 M(μ‐H)(μ‐NMe 2 ) 2 } 2 M], shown in Equation (2). 3b The role of silanes in these reactions is to remove amide ligands as aminosilanes and form MH bonds. We also found that the reactions of Ta(NMe 2 ) 5 with silanes afford the dinuclear Ta–hydride–imine complex [(Me 2 N) 3 Ta(μ‐H) 2 (μ‐ N ‐η 2 ‐ N , C ‐CH 2 NMe)Ta(NMe 2 ) 3 ] ( 1 ) through β‐H elimination [Eq.…”
Section: Introductionmentioning
confidence: 99%